2021
DOI: 10.1101/2020.12.31.424985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The growing topology of theC. elegansconnectome

Abstract: Probing the developing neural circuitry in Caenorhabditis elegans has enhanced our understanding of nervous systems. The C. elegans connectome, like those of other species, is characterized by a rich club of densely connected neurons embedded within a small-world architecture. This organization of neuronal connections, captured by quantitative network statistics, provides insight into the system’s capacity to perform integrative computations. Yet these network measures are limited in their ability to detect we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…What biological mechanisms cause such dramatic differences in motif growth-rate? This points to a "preference" for certain structural properties in immature connectomes, and different local structural property preferences in a mature connectome -compatible with parallel observations on topological changes to a connectome during maturation (11). 8), where the probability of connection is equal to the compared graph's density.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…What biological mechanisms cause such dramatic differences in motif growth-rate? This points to a "preference" for certain structural properties in immature connectomes, and different local structural property preferences in a mature connectome -compatible with parallel observations on topological changes to a connectome during maturation (11). 8), where the probability of connection is equal to the compared graph's density.…”
Section: Discussionsupporting
confidence: 79%
“…The C. elegans connectome is composed of a dense network with inputs predominantly from sensory neurons and outputs predominantly to The adult connectome has significant variability in loop counts. Previous work (10,11) has suggested that loops and cycles are important for computation in the growing nematode connectome. Here, we use our reproducible graph techniques to quantify this property during development, and show that the total number of loops tends to grow as the animal matures.…”
Section: Graph Properties Of a Growing Brain (Tablementioning
confidence: 99%
“…For example, the C. elegans connectome, like those of larger nervous systems, exhibits a small-world topology, with relatively high clustering paired with relatively short average path lengths 49,50 . Likewise, the C. elegans nervous system is highly modular, with functionally segregated local clusters of high within-group connectivity [51][52][53][54] . Finally, the worm connectome contains a small number of highly connected hubs, which are interconnected in a core or rich club and facilitate communication between modules 55 ; similar rich club topology has been observed in bigger brains, including the human cortex 56,57 .…”
Section: Introductionmentioning
confidence: 99%
“…Persistence has been successfully used to study high-dimensional time series, especially those that exhibit some quasi-periodic behavior like the undulation of C. elegans ( Tralie, 2016 ; Tralie and Perea, 2018 ). But to the authors’ knowledge, persistent homology has not been previously used to analyze C. elegans behavior, though it and similar techniques have been used to study C. elegans neural data ( Petri et al, 2013 ; Backholm et al, 2015 ; Sizemore et al, 2019 ; Helm et al, 2020 ; Lütgehetmann et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research into gene expression has used persistent homology to detect patterns or classify whether a signal is periodic ( Dequéant et al, 2008 ; Perea et al, 2015 ). Frequently, persistence has been used to study neural data ( Petri et al, 2013 ; Backholm et al, 2015 ; Stolz et al, 2017 ; Sizemore et al, 2019 ; Helm et al, 2020 ; Lütgehetmann et al, 2020 ), and in many cases neural data from C. elegans , but the analysis tends to rely on clique complexes as the topological space of interest instead of sliding window embeddings.…”
Section: Introductionmentioning
confidence: 99%